UPAYA MENINGKATKAN AKTIVITAS BELAJAR PADA LAYANAN BIMBINGAN DAN KONSELING MATERI STOP BULLYING MELALUI MEDIA AUDIO VISUAL - Samsuri, Samsuri (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2023)
This research is Guidance and Counseling Action Research (PTBK) with the research subjects being all 10 students in class VII of SMPLB Negeri Selatpanjang for the 2021/2022 academic year. The aim of the research is to increase student learning activities in the guidance and counseling service with stop bullying materials. Data collection was carried out using observation and documentation techniques. Data analysis used in this research used qualitative descriptive analysis. The research activities carried out are planning, action, observation and reflection and carried out in 2 cycles. The results of the research data analysis show that the use of audiovisual media in the guidance and counseling services for stop bullying materials for class VII students at SMPLB Negeri Selatpanjang has been proven to increase student learning activities, this is proven by increasing student learning activities at each stage of the cycle where in the initial condition there were 3 students or 30 %, increased in cycle I by 5 students or 50%, and in cycle II there were 8 students or 80% of students who were declared complete. These results are in accordance with the specified indicators, namely the minimum number of students who are declared complete and are at the minimum good and very good assessment criteria which reaches 85% of the total number of students. From the explanation above, it can be concluded that the use of audiovisual media in guidance and counseling services regarding stop bullying has been proven to be able to increase the learning activities of class VII students at SMPLB Negeri Selatpanjang semester 1 of the 2021/2022 school year